Application of Hybrid Extracorporeal Membrane Oxygenation for the Treatment of Subsequent Shock following Acute Respiratory Distress Syndrome Developing after Firearm Injury - Yahya Yildiz; Didem Melis Oztas; Mustafa Ozer Ulukan; Korhan Erkanli; Orcun Unal; Murat Ugurlucan; Halil Turkoglu (Case Reports in Medicine)
The use of extracorporeal membrane oxygenation (ECMO) in acute respiratory distress syndrome (ARDS) and cardio-circulatory shock has been widely accepted. In recent years, a variety of novel and exceptional indications for ECMO have been proposed; however, experience with ECMO use in the presence of multiple penetrating injuries is limited. In this report, we present successful ECMO application in a patient with multiple firearm injuries. Veno-venous ECMO was applied for ARDS and converted to the venoarterial mode when the patient developed septic cardiomyopathy. The clinical status of the patient gradually improved, and the patient was discharged from the hospital after 24 days, successfully.